Safety and efficacy of elvitegravir, dolutegravir, and raltegravir in a real-world cohort of treatment-naïve and -experienced patients. Issue 32 (August 2019) - Brehm, Thomas Theo; Franz, Marleen; Hüfner, Anja; Hertling, Sandra; Schmiedel, Stefan; Degen, Olaf; Kreuels, Benno; Schulze zur Wiesch, Julian
Abstract : Abstract: The aim of this retrospective cohort study was to compare safety, efficacy and rates and reasons of discontinuation of the 3 currently approved integrase strand transfer inhibitors (INSTIs) elvitegravir (EVG), dolutegravir (DTG), and raltegravir (RAL) in HIV-infected treatment-naïve and -experienced patients in a real-world cohort. One hundred four treatment-naïve patients were prescribed an INSTI-based combined antiretroviral therapy (cART)-regimen (first-line group) and 219 patients were switched to an INSTI-based cART-regimen from another treatment regimen (switch group) at our institution between May 2007 and December 2014. Twelve months after initiation of treatment, 92% of patients in the first-line group (EVG: 96%, n = 22/23; DTG: 92%, n = 34/37; RAL: 90%, n = 28/31) and 88% of patients in the switch group (EVG: 94%, n = 32/34; DTG: 90%, n = 69/77; RAL: 85%, n = 67/79) showed full virological suppression (viral load <50 copies/mL). Side effects of any kind occurred in 12% (n = 12/104) of patients in the first-line group, and 10% (n = 21/219) of patients in the switch group. In the switch group neuropsychiatric side effects (depression, vertigo, and sleep disturbances) occurred more frequently in patients treated with DTG (11%, n = 10) compared to the 2 other INSTI-based cART-regimen (EVG: 2%, n = 1; RAL: 1%, n = 1). Side effects only rarely led to discontinuation of treatment (first-line-group: 2%, n = 2/104; switch-group: 1%, n = 3/219). In this real-world setting, INSTI-based ART-regimens were highly efficacious with no significant differences between any of the 3 INSTIs. Overall, side effects were only rarely observed and generally mild in all subgroups. In light of a slightly higher incidence of vertigo and sleep disturbances in patients switched to DTG, awareness of the potential onset of psychiatric symptoms is warranted during follow-up in those patients. Abstract : Supplemental Digital Content is available in the text